SOSIALISASI PENTINGNYA REKAM MEDIS DI FASILITAS LAYANAN KESEHATAN PADA SISWA SMAN 1 TELUK SEBONG - Anisa, Desfa; Farhansyah, Fani; Wulandari, Siti (Transpublika Publisher, 2023)
A medical record is a record that contains the patient's identity, patient diagnosis, treatment and services provided to the patient during the patient's treatment at a hospital, health center or clinic. Medical records are not just filling in patient medical data, but also coding the disease. The coding is done so that health facilities can claim the costs incurred in treating a patient. The quality of medical recorders is very important because it can determine the quality of service at health facilities. So, it is necessary to provide an understanding of medical records to the community so that later many people will better understand how important medical records are for patients in health facilities. This socialization activity went smoothly and all participants seemed enthusiastic in listening to the material presented. The method used in this activity is in the form of socialization and question and answer. The participants who participated in this activity were students of SMAN 1 Teluk. The purpose of this activity is to socialize the students of SMAN 1 Teluk Sebong about the importance of medical records.